INTERNALISASI NILAI KESADARAN LINGKUNGAN MELALUI BIOGRAFI SEBAGAI SUMBER BELAJAR IPS DI SMPN 5 BANJARMASIN - Putra, Muhammad Adhitya Hidayat; Mattiro, Syahlan; Alfisyah, Alfisyah; P, Reski; Budiarti, Ayu (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Environmental Awareness is an effort that involves every citizen in growing and fostering awareness to preserve the environment. Humans are very dependent on the natural environment. Students who still lack environmental understanding and do not want to protect their surroundings. We need to teach this through education to students an understanding of environmental awareness. Through the biography of Ir. Pangeran Mohamad Noor, the value of awareness that he has should be used as a source of social studies learning so that students gain an understanding of environmental awareness. The results of this study, the biography of Ir. P. M. Noor, the value of environmental awareness possessed by Ir. P. M Noor, there are 3, namely: Hard Work Value, Environmental Care Value, and Responsibility Value. These values can be used as a source of social studies learning so that students gain an understanding of the environment through Ir. P. M Noor. Based on the study, it can be concluded that the value of environmental awareness through the biography of Ir. Pangeran Mohamad Noor is relevant to be used as a source of social studies learning at SMP Negeri 5 Banjarmasin with the teacher analyzing the RPP first and including these values in social studies learning as a source of social studies learning.